Non-steroidal anti-inflammatory drug delays corneal wound healing by reducing production of 12-hydroxyheptadecatrienoic acid, a ligand for leukotriene B(4) receptor 2 - Iwamoto, Satoshi (Sci Rep, 2017)
Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used to reduce inflammation by suppressing cyclooxygenases (COXs). NSAID eye drops are frequently prescribed after ocular surgery to reduce inflammation and pain, but this treatment has clinically significant side effects, including corneal ulcer and perforation. The molecular mechanisms underlying these side effects remain unknown. Recently, the COX product 12(S)-hydroxyheptadeca-5Z,8E,10E-trienoic acid (12-HHT) was identified as an endogenous ligand for leukotriene B(4) receptor 2 (BLT2), which is important in maintenance of epithelial homeostasis. We hypothesized that NSAID-dependent corneal damage is caused by reduced production of 12-HHT. Diclofenac eye drops decreased the abundance of downstream products of COX and delayed corneal wound healing in BALB/c mice. Expression of BLT2 was observed in murine ocular tissues including cornea, and in human corneal epithelial cell line and human primary corneal epithelial cells. In BLT2-knockout mice, corneal wound healing was delayed, but the diclofenac-dependent delay in corneal wound healing disappeared. 12-HHT accelerated wound closure both in BLT2-transfected corneal cell line and human primary corneal epithelial cells. Thus, our results reveal that NSAIDs delay corneal wound healing by inhibiting 12-HHT production, and suggest that stimulation of the 12-HHT/BLT2 axis represents a novel therapeutic approach to corneal wound healing.